Effect of fixative type and fixation time on the morphology of equine preantral ovarian follicles - Búfalo, Isabela; González, Suellen Miguez; Silva, Camila Bizarro; Lindquist, Andressa Guidugli; Bergamo, Larissa Zamparone; Costa, Camila Bortoliero; Marinho, Luciana Simões Rafagnin; Seneda, Marcelo Marcondes (Semina: Ciências Agrárias, 2016)
The aim of this study was to investigate the efficacy of the tissue fixatives Bouin, Carnoy and 10% Formaldehyde in equine ovarian fragments. Ovaries (n=4) from mares of mixed breeds were obtained at a local slaughterhouse and transported at 20 ºC in a thermo container. Immediately after collection, the ovaries were washed with a modified PBS solution (CultilabÂ®, Campinas-SP, Brazil) and divided into nine fragments with approximately 5x5x1 mm, removed from the parenchyma of each ovary. The ovarian fragments were then immersed in three different fixatives, Bouin (B) Carnoy (C) or 10% Formaldehyde (F) for 6, 12 or 24 hours. Each fragment was individually immersed in a 20 mL tube containing 20 times the volume of fixative solution. After this period, the fragments were held in 70% ethanol for 24 hours. Each procedure was performed in four replicates. For histological analysis, the specimens were dehydrated in increasing concentrations of alcohol, submitted to diaphanization in xylol and embedded in paraffin. Serial sections of 5 ?m were made with the use of a rotating microtome (LeicaÂ® type, Wetzlar, Germany), followed by slide mounting and staining with periodic acid-Schiff (PAS) and hematoxylin. A total of 540 slides with 1,620 sections were evaluated, which contained 465 preantral follicles that were classified as normal or degenerated. Follicles were considered as degenerated when presented at least one of the following aspects: cytoplasm retraction, pyknotic nucleus, cytoplasmic vacuoles, displacement of granulosa cells and/or disruption of the basal membrane. A logistic regression test was used for statistical analysis, and differences were considered significant when P<0.05. The Carnoy fixative, when used for 24 hours, provided the best conditions of morphological integrity (53.3%; 32/60) compared to all others, and the use of Boiun for 24 hours was considered the worst treatment (19.1%; 9/47). The other treatments lead to the following results: C12h 50% (30/60), C6 H 40% (24/60), F24h 37.8% (17/45), F12h 35.1% (13/37), F6h 32% (16/50), B12h 30.5% (18/59) and B6h 24.4% (11/45). Therefore, we suggest that fixation of equine ovarian tissue with Carnoy for 24 hours is the most suitable protocol for morphological preservation of pre-antral follicles.